ANALISIS RISIKO PANEN TANDAN BUAH SEGAR KELAPA SAWIT MENGGUNAKAN METODE Failure Mode and Effect Analysis (FMEA) DI AFDELING OA (ALPA) PADA PT. KARYA TANAH SUBUR - Wianda Agil Rahayu Smed; Teuku Athaillah (Universitas Medan Area, 2023)
One of the factors that affect productivity in oil palm plantations is the harvest factor. Harvest management needs to be considered to reduce yield loss. Risks occur in oil palm harvesting, especially in harvesting activities that are not in accordance with standard operating procedures. Harvesting problems that are not in accordance with Standard Operating Procedures (SOP) result in reduced Fresh Fruit Bunches (FFB) production such as unripe fruit, rotten fruit, loose fruit, leftover and long stalks. This study aims to determine the risks of harvesting fresh fruit bunches of oil palm at PT. Karya Tanah Subur. The data used in this study are primary data and secondary data. The data analysis method used is the Failure Mode and Effect Analysis (FMEA) method to identify the type of risk and look for the resulting effects. The results of this study indicate that there are three priority risk components to be resolved immediately for Afdeling Alpa (OA) PT. Karya Tanah Subur. The first priority is for the risk of harvesting unripe fruit with a critical risk level with RPN of 324, the second priority is for harvesting rotten fruit with a critical risk level with RPN of 280 and the third priority is for harvesting with long stalks with a critical risk with RPN of 245. These risks can be handled by the company according to priority.